Forty-year Tunisian bibliometrics of general surgery theses in the four national faculties of medicine (1980–2019). Issue 1 (1st January 2022) - Azzaza, Mohamed; Ben Mabrouk, Ghofrane; Chebil, Dhekra; Nouira, Sarra; Melki, Sarra; El Haddad, Nihel; Ben Abdelaziz, Ahmed
ABSTRACT: The objective of this work was to establish the bibliometric profile of Tunisian theses in 'general surgery' and to describe their themes, their study designs, and their writing quality. This is a retrospective descriptive bibliometric study, covering all the theses in medicine in the specialty of 'general surgery', defended in the four medical faculties of Tunisia, during the forty last years from 1980 to 2019. During the study period, 739 theses in 'general surgery' were discussed in Tunisia, with an average of 19 theses per year. The most studied research topic was emergencies (41%), followed by common surgical pathologies (26%) and digestive oncology (21.5%). Descriptive studies and case studies represented the majority of study designs with respective proportions of 56.9% and 40.6%. Only 20.7% of these theses had a scientific writing quality deemed satisfactory. The least respected elements in writing their summaries were statistical (confidence intervals and standard deviations) and documentary (keywords). Despite the plethora of themes of Tunisian theses in 'general surgery', their basic methodology and their editorial non conformity require the educational reform of the dissertations, both doctoral students and supervisors, by strengthening their skills in research methodology and scientific communication written.